2023
DOI: 10.2196/46286
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Mobile Phone–Based Physical Activity Program for Treating Depression, Stress, Psychological Well-Being, and Quality of Life Among Adults: Quantitative Study

Abstract: Background Depression is a substantial global health problem, affecting >300 million people and resulting in 12.7% of all deaths. Depression causes various physical and cognitive problems, leading to a 5-year to 10-year decrease in life expectancy compared with the general population. Physical activity is known to be an effective, evidence-based treatment for depression. However, people generally have difficulties with participating in physical activity owing to limitations in time and accessibi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…As a result, those who participate in both the progressive and fixed PA groups may observe a more significant decrease in depression and perceived stress compared with those who do not engage in PA. Previous literature has found the significant impact of mobile-based PA programs on mental health [ 36 - 41 ], and this aligns with the findings of this study. Theoretical implications of these findings in academia endorse the use of both regular fixed PA and progressive PA through mobile apps as potential therapies for mitigating depression and stress.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As a result, those who participate in both the progressive and fixed PA groups may observe a more significant decrease in depression and perceived stress compared with those who do not engage in PA. Previous literature has found the significant impact of mobile-based PA programs on mental health [ 36 - 41 ], and this aligns with the findings of this study. Theoretical implications of these findings in academia endorse the use of both regular fixed PA and progressive PA through mobile apps as potential therapies for mitigating depression and stress.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the appropriate sample size was determined using the G* power calculator (version 3.1.9.4; Heinrich-Heine-Universität) [ 45 ]. The aim was to achieve a significance level of .05 and a statistical power of 95%, with an effect size of 0.36, based on the data from a prior study that investigated the impact of mobile-based PA interventions on depression [ 41 ]. The calculations indicated that 30 participants were required to reach the desired power of 0.95.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation